Dueling to the End/Ending "The Duel". - Lawtoo, Nidesh (Contagion: Journal of Violence, Mimesis & Culture, 2015)
The article looks at the literary work "Achever Clausewitz" by philosopher René Girard which discusses the dynamic of mimetic violence. Topics mentioned include Girard's attempts to finish the work of fellow philosopher Carl von Clausewitz on the dynamic of war, an overview of his original theory of mimesis in literary studies, and the depiction of mimetic doubles in the novel "Heart of Darkness" by Joseph Conrad.